International REgistry to assess medical Practice with lOngitudinal obseRvation for Treatment of Heart Failure (REPORT‐HF): rationale for and design of a global registry. (10th March 2015) - Filippatos, Gerasimos; Khan, Sadiya Sana; Ambrosy, Andrew P.; Cleland, John G.F.; Collins, Sean P.; Lam, Carolyn S.P.; Angermann, Christiane E.; Ertl, Georg; Dahlström, Ulf; Hu, Dayi; Dickstein, Kenneth; Perrone, Sergio V.; et al.
Abstract : Aims: The clinical characteristics, initial presentation, management, and outcomes of patients hospitalized with new‐onset (first diagnosis) heart failure (HF) or decompensation of chronic HF are poorly understood worldwide. REPORT‐HF (International REgistry to assess medical Practice with lOngitudinal obseRvation for Treatment of Heart Failure) is a global, prospective, and observational study designed to characterize patient trajectories longitudinally during and following an index hospitalization for HF. Methods: Data collection for the registry will be conducted at ∼300 sites located in ∼40 countries. Comprehensive data including demographics, clinical presentation, co‐morbidities, treatment patterns, quality of life, in‐hospital and post‐discharge outcomes, and health utilization and costs will be collected. Enrolment of ∼20 000 adult patients hospitalized with new‐onset (first diagnosis) HF or decompensation of chronic HF over a 3‐year period is planned with subsequent 3 years follow‐up. Perspective: The REPORT‐HF registry will explore the clinical characteristics, management, and outcomes of HF worldwide. This global research programme may have implications for the formulation of public health policy and the design and conduct of international clinical trials.